1476. Impact of an Educational Campaign on Rates of Sputum Culture Acquisition as an Opportunity for Antibiotic De-escalation. (31st December 2020) - Snawerdt, Jessica; Bremmer, Derek N; Carr, Dustin R; Walsh, Thomas L; Trienski, Tamara; Buchanan, Carley
Abstract: Background: The 2019 community-acquired pneumonia (CAP) guidelines recommend obtaining a sputum culture in patients who are empirically treated for methicillin-resistant Staphylococcus aureus (MRSA) or Pseudomonas aeruginosa to assist clinicians in optimizing antimicrobial therapy. A previous study at our institution found respiratory cultures were rarely obtained in patients with CAP. As a result of these findings, an educational campaign was implemented to promote the use of an induced sputum protocol. Methods: This was a multicenter, retrospective cohort study that included patients who were ≥18 years of age, had a diagnosis of CAP, and received ≥48 hours of anti-pseudomonal antibiotics. Patients were excluded if mechanically ventilated within 48 hours of admission or diagnosed with hospital-acquired or ventilator-associated pneumonia. Patients were grouped into pre- and post-intervention time periods. The intervention involved education on obtaining respiratory cultures including technique on induced sputums and updates to CAP order sets. The primary outcome was the rate of sputum culture acquisition. Secondary outcomes included duration of anti-pseudomonal and anti-MRSA therapy, in-hospital mortality, and length of stay. Results: A total of 143 patients met inclusion criteria, 72 in the pre-implementation group and 71 in the post-implementation group. Baseline characteristics were similar between the two groups. More patients in the post-implementation group had a sputum culture obtained but the difference was not statistically significant (38.9% vs 53.5%; p=0.08). Anti-pseudomonal therapy was continued for an average of 5.6 days pre-implementation and 5.2 days post-implementation (p=0.499). There was also not a significant difference in anti-MRSA duration between the two groups (3.4 days vs 3.2 days; p=0.606). In-hospital mortality and length of stay were similar between the two groups. Conclusion: An educational campaign focusing on the acquisition of induced sputums led to an increase in rates of sputum cultures collected. However, this did not correlate with a decrease in duration of anti-MRSA or anti-pseudomonal therapy. Further interventions should be made to optimize de-escalation of broad spectrum antibiotics based on sputum culture results. Disclosures: All Authors : No reported disclosures